Corner entry - Ellis, S. (1999)
Entering into the corner is dependant upon many factors: speed, age, size, whether you are skating anoffensive track to get as much speed as possible, or defending your entry to prevent a pass at that point. Here are some advices how rto master this technique. Generally, the slower the pace the less the need to take a wide entry as the centrifugal force (the force that pulls you away from the corner) is not as great. As the pace gets faster you may want to take a wider entry to lessen the centrifugal force or to be able to hold tight to the blocks at the end of the turn. The entry also depends on your ability to carve a corner at very high speed. Derrick Campbell is probably the best in the world at being able to hold tight turns without losing a lot of speed because of his ability to pivot, whereas Fred Blackburn generates the most speed by skating very wide entries and exits. A good lean is crucial to generating speed on the corner. A common mistake young skaters make is to plant the left foot for the corner entry with the flat of the blade on the ice and the body still upright. This forces the skater to push upwards instead of to the side and is not very effective. Make sure that when you finish your last straightaway push with the right foot you are already in the leaning position you will maintain throughout the entire turn. The left foot should come down onto the ice on its left edge and be pointing slightly into the turn already. Many skaters make the mistake of "diving" into the corner. That is, reaching towards the corner with the left hand and shoulder. All this does is put you up on your toes, rotates the shoulders away from the turn and causes you to slow down, or worse, to fall. Be patient - let the corner come to you. Don't reach for it. Maintain that good basic position and simply lean into the turn. When to actually start the corner depends on all the factors mentioned above. A general guide is to draw a line from apex through the first block and another from apex through the second block (Fig. A). This is where the left foot normally enters the corner. Starting the corner any earlier means that you will not be able to lean enough as you are essentially still on the straight. It also forces you into the first part of the turn too early and you will have to change direction to get around the apex. If you find you can't get far enough down the straight to enter the corner at this point try adding an extra crossover on the exit or reaching up the straight further with each thrust. As a last resort you may need to add more straightaway strides. Your path from the entry point should take you in a gradual arc to the apex block. At this point your left foot should pass by the block very closely. Figures B and C show two different stride patterns for the corner. Fig. B is typical of a younger skater or an older skater at high speed, while Fig. C is that of an older skater at a slow speed. Skaters should experiment to see what the best stride pattern is for them for different situations and practice these patterns often. What works at 75% speed may not work at 100%.